Sampling for Asian citrus psyllid (ACP) in Florida citrus groves - H. Alejandro Arevalo; Jawwad A. Qureshi; Philip A. Stansly (EDIS)
Three techniques are currently in use to sample adult Asian citrus psyllids (ACP). This 7-page illustrated fact sheet by H. A. Arevalo, J. A. Qureshi, and P. A. Stansly discusses the strengths and weaknesses of each and makes recommendations for routine monitoring of ACP for management purposes. Includes references. Published by the UF Department of Entomology and Nematology, September 2010.